An educational curriculum by using computers to develop the level of and cognitive performance skill of football matches referees - Shaheed Radhi, Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
The use of modern scientific technologies (computers) is one of the educational means that have a direct impact on the learning process, as this technology adds a lot to the educational process through its highly efficient capabilities in providing the best as well as saving effort and time and being a factor of fun and excitement. By following the researcher in the football game, he found that there is a weakness in the skill and cognitive performance of the arbitration skills in this game as a result of the coaches’ reliance on the use of means of presentation (live model), explanation, and clarification, which may not allow the learner or the novice referee to understand, comprehend, and perceive the minute details of performance. Technical and cognitive skills, which led the researcher to introduce a computer to learn the skills of soccer referees after preparing an educational curriculum that includes learning the technical and cognitive performance of refereeing skills.